Models forecasting the content of humus on the basis of structural bonds of properties in soils of light texture - Natalya M. Mudrykh, Iraida A. Samofalova (International Journal of Advanced Science and Technology, 2020)
Soils of light texture are characterized by instability to the influence of external factors, which change their properties. The relevance of the research consists in creating models of forecast that will allow us to quickly and timely make management decisions for maintaining soil fertility. In this regard, the article is aimed at identifying the structural bonds of properties in soils of light texture for forecasting the humus content change. The studies on the spatial variability of the soil properties in the non-chernozem zone (for example, LLC “Selskoye”, Solikamsky District, Perm Region) are given. The qualitative properties variation indicators of the mineral composition in soils of light texture were significant within the field. The calculation of the models of forecast for the humus content was carried out, using different methods: correlation and information-logical. With the help of the correlation coefficient, linear structural bonds have been established between the soil properties, which indicated, that the humus content in light soils largely depends on the availability of the plant nutrition elements. The use of the information-logical method allowed us to identify other structural bonds of the soil properties and establish two regularities for soils of light texture. First regularity: the level of humus content in the soil affects the degree of spatial heterogeneity of physicochemical and agrochemical parameters. Second regularity: the humus content is primarily determined by the content of exchange cations, then by the content of mobile phosphorus, by exchangeable potassium, and, lastly, by the acidic properties of the soil. Adequate models of forecast for the prediction of humus content were obtained depending on the indicators of the exchange acidity, the sum of exchange cations and nutrients for the agro-sod-podzolic soils of light texture. If it is necessary to promptly change the fertilizer system, producers of agricultural products, basing on soil patterns and (or) determining indicators of soil properties, can predict the level of humus and (or) mineral nitrogen in the soil. These models of forecast can be the basis for planning measures to improve soil fertility at specific work sites and for recommending differentiated application of organic and mineral fertilizers.